Difference in Indonesian and Malaysian University Students’ Psychological Well-Being During Covid-19 Pandemic - Farozin, Muh; Suwarjo, Suwarjo; Purnama, Diana Septi; Astuti, Budi; Lestari, Rizqi; Mansur, Muhamad (Psikopedagogia, 2022)
Many countries worldwide undergo changes in various sectors due Covid-19 pandemic, including Indonesia and Malaysia. The pandemic also affects university students’ physical and psychological aspects. This comparative study attempted to find out the difference in university students’ psychological well-being during the Covid-19 pandemic. The population of this study was university students of Universitas Negeri Yogyakarta, Indonesia, and Universitas Pendidikan Sultan Idris, Malaysia. Six hundred-one university students were recruited using an accidental sampling technique. The data were collected using psychological well-being scale. Mann-Whitney test was performed to determine the difference in students’ psychological well-being in the two universities. The study result showed a p-value of 0.000 (< 0.05), indicating a difference in students’ psychological well-being at Universitas Negeri Yogyakarta and Universitas Pendidikan Sultan Idris. This study result is expected to provide a depiction of students’ psychological well-being during the covid-19 pandemic.